Empirical Study and Response Strategies of Open Access Transformation in Chinese University Libraries - Jing GUO, Yihua ZHANG, Yaqi SHEN, Haiyan SONG (Nongye tushu qingbao xuebao)
[Purpose/Significance] With the advancement of open science, the signing of transformative open access agreements will have a profound and long-term impact on the acquisition of library information resources. How libraries respond to this trend, how to evaluate open access conversion agreements, whether to sign reasonable open access conversion agreements, and actively adopt them suitable for China's domestic conditions, and scientific and effective collection acquisition and transformation strategies in an open publishing environment, how to ensure reasonable investment of institutional publishing funds, and how to play a role in promoting positive academic exchanges in an open scientific environment are all important issues that deserve industry attention and exploration. [Method/Process] We first reviewed the research progress on open access transformation at home and abroad. Second, based on the data statistics and analysis of DOAJ and related research reports and institutions, the relatiave concepts were elaborated, the impact on stakeholders was examined, and the trend of practical development was understood. Through the analysis and induction of practical cases in domestic and foreign university libraries, especially through the case analysis of the library of Shanghai Jiao Tong University, we elaborated on the issues that Chinese university libraries need to pay more attention to in the process of open access transformation, and proposes related strategies. [Results/Conclusions] To cope with the open access movement, on the one hand, we need to be vigilant against the emergence of new knowledge "barriers" and "paywalls" due to profit-driven, high APC, and transformative costs, as well as the lack of regulatory norms for author payments and the existence of financial risks and loopholes such as taxation. On the other hand, all parties adhere to the original intention of promoting the dissemination of academic knowledge, forming a transparent and reasonable APC price ecological market, establishing a hierarchical, reliable, and sustainable open publishing funding support, transformation, and regulation mechanism, and creating an economic and healthy academic information exchange environment. In this process, it is necessary for university libraries to comprehensively coordinate subscription fees and publishing fees, and fully guarantee and restructure knowledge exchange and information dissemination. This paper summarizes the three issues that need to be considered in the process of open access transformation, including the impact of open access on stakeholders, the phenomena that need to be monitored, and the key to ensuring sustainability. We proposed implementation strategies based on practical cases, including research and data preparation, analysis and evaluation, focusing on specific implementation points such as controlling elements of contract terms. The OA transformation is still in the transition period, and in order to avoid the loss of funds due to double payments, some overall management and guidance systems are needed during this period. For some publishers that prioritize commercial profit, it is necessary to send strong signals and strengthen supervision of APC pricing rationality through alliances and other levels. In addtion, we must strengthen China's leadership and discourse power in open science, and carry out the construction of related supporting systems.